Waste biomass toward hydrogen fuel supply chain management for electricity: Malaysia perspective - Zakaria, Izatul Husna; Ibrahim, Jafni Azhan; Othman, Abdul Aziz (2016)
Green energy is becoming an important aspect of every country in the world toward energy security by reducing dependence on fossil fuel import and enhancing better life quality by living in the healthy environment.This conceptual paper is an approach toward determining physical flow’s characteristic of waste wood biomass in high scale plantation toward producing gas fuel for electricity using gasification technique.The scope of this study is supply chain management of syngas fuel from wood waste biomass using direct gasification conversion technology. Literature review on energy security, Malaysia’s energy mix, Biomass SCM and technology.This paper uses the theoretical framework of a model of transportation (Lumsden, 2006) and the function of the terminal (Hulten, 1997) for research purpose. To incorporate biomass unique properties, Biomass Element Life Cycle Analysis (BELCA) which is a novel technique develop to understand the behaviour of biomass supply. Theoretical framework used to answer the research questions are Supply Chain Operations Reference (SCOR) framework and Sustainable strategy development in supply chain management framework